A practical procedure to estimate the quality and the adverse impact of single-stage selection decisions - DE CORTE, Wilfried (Institutional Knowledge at Singapore Management University, 2003)
The quandary posed by the conflicting goals of valid selection and a diverse workforce is one of the most perplexing problems facing the practice of personnel selection today. To help address the issue, the article presents a comprehensive method and a related computer program to estimate the expected adverse impact and the expected quality of the majority, the minority and the total selected work force. Compared to previous related procedures, the present method is much more general as it can address situations with both multiple predictor and multiple criterion dimensions. In addition, the expected effects can be computed given the overall selection ratio and the estimates are derived analytically and, hence, are accurate. To assist the selection practitioner, the method is made available as a free download from the Internet.